Alüminyum kaplama için soya fasulyesi yağı bazlı fotokürlenebilir poliüretan akrilatların sentezi ve uygulaması - Ozer, Berivan; Kuş, Betül Nur; Yetman, Pelin; Demircioğlu, Müslüm; Eryılmaz, Oğuz; Sancak, Erhan; Yıldız, Zehra (İdris Karagöz, 2025)
Bu çalışmada, ilk olarak akrilik asit (AA) ve epoksitlenmiş soya fasulyesi yağı (ESBO) reaksiyona sokulmuştur. Daha sonra elde edilen akrillenmiş ESBO (AESBO) oligomeri, 2,4-toluen diizosiyanat - 2-hidroksietil metakrilat (TDI-HEMA) ara ürününün izosiyanat grupları ile reaksiyona sokulmuştur. TDI, küresel poliüretan endüstrisinde en yaygın olarak üretilen ve kullanılan izosiyanat formu olduğu için izosiyanat kaynağı olarak seçilmiştir. HEMA, sırasıyla UV kürleme ve poliüretan üretimi için gereken hidroksil ve akrilat gruplarını sağlamıştır. Ayrıca oligomer, HEMA'nın metil yan grubu nedeniyle esnektir. Kaplama formülasyonları, sentezlenen TDI-HEMA modifiye AESBO oligomerinin yanı sıra çeşitli reaktif seyrelticiler ve bir foto başlatıcı içermektedir. Hazırlanan formülasyonlar alüminyum plakalar üzerine sprey kaplama ile uygulanmış ve UV ışığı ile kürlenmiştir. Reaktif seyreltici türünün film oluşturma ve kaplama performansı üzerindeki etkisi araştırılmıştır.

The aim of this work is to create a new bio-based photocurable oligomer by starting with soybean oil instead of petroleum-based chemicals. For this purpose, acrylic acid (AA) and epoxidized soybean oil (ESBO) were initially reacted. Then the obtained acrylated ESBO (AESBO) oligomer was reacted with the isocyanate groups of the 2,4-toluene diisocyanate - 2-hydroxyethyl methacrylate (TDI-HEMA) adduct. TDI was chosen as the isocyanate source since it is the most widely produced and used form of isocyanate in the global polyurethane industry. HEMA provided the hydroxyl and acrylate groups needed for UV curing and polyurethane production, respectively. Additionally, the oligomer is flexible due to the methyl side group of HEMA. The synthesized oligomer was characterized by Fourier transform infrared (FTIR) spectroscopy and differential scanning calorimetry (DSC) analysis. The coating compositions included the produced TDI-HEMA modified AESBO oligomer, as well as a variety of reactive diluents and a photoinitiator. Then formulations were applied on aluminum plates by spray coating and cured by UV light. The impact of the type of reactive diluent on the film forming and coating performance were all searched. Overall results proved that the inclusion of reactive diluents in the coating formulations helped to increase the coating quality and performance by adjusting the crosslinking density resulting in enhancement in adhesion.
Synthesis and application of soybean oil based photocurable polyurethane acrylates for aluminum coating
This study was financially supported by TÜBITAK IRA-SME project with the grant number “122N399”.
Keywords: Polymer Science and Technologies; Polimer Bilimi ve Teknolojileri